Virtual atlas of avian pathology - Chacón Silva, Mónica Isabel; Higuera Ángel, Fernando; Sanabria Naranjo, Fernando; Mejía Torres, Julián Adolfo (Spei Domus, 2011)
The objective of this work was to design and elaborate an atlas of avian pathology. Students, teachers, and graduates from the Faculty of veterinary medicine and zootecnics of the Universidad Cooperativa de Colombia, Bucaramanga branch. Contributed collected information for the creation of the atlas during the years 2009-2010. Computer experts were in charge of the structure of the atlas that was based upon study of the surroundings. There were three stages: first an analysis stage, during which the consulted components: texts, graphs, and videos were used to clarify each of the elements of the multimedia atlas. In the design stage we defined the moduli and processes, and incorporated pedagogical variables. In the construction stage, we integrated all the components: text, videos and animations and we made preliminary tests of the system. Results: The atlas was conformed in the following way: Viral diseases (18 topics), bacterial diseases (10 topics), mycosis and mycotoxicosis (4 topics), protozoal diseases (4 topics), internal and external parasites (2 topics), mixed and metabolic disorders (18 topics), and vaccines (3 topics). We were able to conclude that the atlas of avian pathology, as a multimedia tool, facilitates the application of new technologies to higher education. This tool breaks the paradigm and the conceptions of traditional education and allows an easy, didactic approach to the teaching and learning process.